Notary Responsibilities for Making Deeds Based on False Statements (Case Study of Decision Number: 782/PDT.G/2020/PN JKT.SEL) - Eztha Oke Sonia; Mella Ismelina Farma Rahayu (PT Publikasiku Academic Solution, 2023)
Notaries are public officials (openbare ambtenaren) appointed by the Ministry of Law and Human Rights (KEMENKUMHAM) who have the authority to make authentic deeds. The notary deed clearly explains the rights and obligations of the parties so that the notary deed becomes the strongest and most complete means of evidence because it can prove the truth of its contents compared to a deed made privately. If a Notary as a public official is proven to have made a mistake in the deed they made, then as a result of their actions they can be held accountable both criminally and civilly if it causes a loss. In the case of the South Jakarta District Court decision number 782/PDT.G/2020/PN JKT.SEL a Notary in Tangerang was involved in a civil case of unlawful acts that resulted in the deed’s cancellation. A notary deed that is canceled by a court decision does not mean the result of a notary's mistake in making the deed, but can also be caused by an error or negligence on the part of the parties resulting in a lawsuit because the notary has made the deed in accordance with the regulations. The notary as a public official has the right to refuse not to notify the contents of the deed in accordance with the oath of office they uttered and taking the minutes of the deed and calling the notary must go through the approval of Notary Honorary Council as an institution that has the authority to carry out guidance and supervision of the notary and the existence of the right of refusal. become a form of legal protection for Notaries when carrying out their duties. This study uses normative legal research methods, by analyzing court decisions as the primary legal.